Analysis of the Role of Single Mothers in Promoting Gender Equality in the Women's Community on Instagram - Hayu Lusianawati; Husen Mony (West Science Social and Humanities Studies, 2025)
Social media, particularly Instagram, has evolved into a strategic digital public space for social advocacy and the formation of critical awareness regarding gender equality. Amidst these dynamics, single mothers have emerged as social actors who not only face the structural burdens of patriarchy but also actively produce alternative narratives about women, family, and gender justice. This article aims to analyze the role of single mothers in promoting gender equality through women's communities on Instagram using a text analysis approach. This study integrates critical discourse analysis, visual representation, and audience interaction analysis of Instagram content produced by the single mother community. Theoretically, this research is grounded in Uses and Gratifications Theory, representation theory, digital feminism, and virtual community theory. The results of the literature review indicate that although studies on gender and Instagram have developed significantly, research specifically positioning single mothers as agents of gender equality advocacy is still limited. This article offers an integrative conceptual model that explains how single mothers' digital narratives contribute to the formation of public awareness and attitudes regarding gender equality. These findings are expected to enrich the academic discourse on communication, gender, and digital media and serve as a reference for further empirically based research.